2020
DOI: 10.3390/ma13051066
|View full text |Cite
|
Sign up to set email alerts
|

Esthetic and Physical Changes of Innovative Titanium Surface Properties Obtained with Laser Technology

Abstract: Aim: The purpose of the study was the evaluation of the esthetic and physical changes produced on colored titanium Grade 5 (Ti6Al4V) laser treated surfaces to be used in implant dentistry for esthetic success. Materials and methods: Colored titanium surfaces were obtained with laser treatment. The physical and topographic properties were evaluated by stereo, light, and electron microscopy and profilometric analyses. L*a*b* colorimetric coordinates were measured by spectrometry, and the superficial chemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The widespread use of dental implants is being improved by technological innovations that mitigate long-term prognoses and the risk of poor alveolar bone conditions. Such innovations include the development of new implant surface textures [2,3] and shapes (e.g., threading [4,5] and platforms [6]) that further improve alveolar ridge augmentation and sinus lift surgeries as pre-implant procedures for alveolar bone atrophy cases [7][8][9]. The growing demand for dental implants has led many manufacturers to enter the industry.…”
Section: Introductionmentioning
confidence: 99%
“…The widespread use of dental implants is being improved by technological innovations that mitigate long-term prognoses and the risk of poor alveolar bone conditions. Such innovations include the development of new implant surface textures [2,3] and shapes (e.g., threading [4,5] and platforms [6]) that further improve alveolar ridge augmentation and sinus lift surgeries as pre-implant procedures for alveolar bone atrophy cases [7][8][9]. The growing demand for dental implants has led many manufacturers to enter the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has a strong mechanical resistance (breaking load of 730–950 N/cm 2 ) and a consequent elongation of 12% breakage. The elastic modulus is low enough and very similar to that of bone (110.000 N/cm 2 ) [ 33 , 34 , 35 ]. Typical characteristics of this metal are the high resistance of corrosion and the high degree of biocompatibility.…”
Section: General Properties Of Titaniummentioning
confidence: 99%
“…Among the most frequent conditions of oral disorders, it is possible to include edentulism. The results of the Global Burden of Disease Study 2010 showed a constant decrease in DALY rates for edentulism in the population standardized by age (Disability Adjusted innovative and alternative titanium laser treatments having various colors are possible and able to produce a complete palette of colors [8] with different optical and physical features [13,23,24,29,30]. The coloring procedure itself is simple and based on the adopted laser power.…”
Section: Introductionmentioning
confidence: 99%